2008
DOI: 10.1080/03031853.2008.9523794
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of off-farm participation decision of farm households in Ethiopia

Abstract: This study analyses the determinants of off-farm work participation decisions of farm households in Ethiopia. A bivariate probit model is applied to account for the simultaneity of participation decisions of both male and female members of farm households. The results of the analysis show that human capital variables such as health and training on non-farm activities have a positive effect on the off-farm participation decisions of male members of farm households. The education status of the head has no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
78
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 8 publications
16
78
2
1
Order By: Relevance
“…Female-headed households are more likely to participate in off-farm activities than the male-headed counterparts because female-headed families engage in off-farm activities to offset their relative lower farm income compared to male-headed ones. However, this is against the result found by Beyene (2008).…”
Section: Determinants Of Participation In Off-farm Activitiescontrasting
confidence: 57%
See 1 more Smart Citation
“…Female-headed households are more likely to participate in off-farm activities than the male-headed counterparts because female-headed families engage in off-farm activities to offset their relative lower farm income compared to male-headed ones. However, this is against the result found by Beyene (2008).…”
Section: Determinants Of Participation In Off-farm Activitiescontrasting
confidence: 57%
“…Therefore, the results of this study adds to the existing literature (e.g., Abate et al 2016;Barrett et al 2001;Beyene 2008;Feng et al 2010) through identifying the factors affecting the participation in off-farm activities. As the study evaluates the impact of participation in off-farm activities on the TE of maize producers, the study indicates the relationship between off-farm and on-farm activities and indicates whether there exists trade-off or complementarity between the two incomegenerating activities.…”
mentioning
confidence: 67%
“…The inclusive causal relationship between livelihood strategies and family structure has been described in many studies. For instance, Beyene (2008) indicated that a farm household in Ethiopia with a large number of dependents was less likely to participate in off-farm work [37].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Studies by Kassie et al (2017), Atamanova and Van den Berg (2012), Beyene, (2008) and Niboye, (2003 observed that, lack of land for farming increases the demand for livelihoods diversification outside agriculture. In fact, people are prompted to consider available options in the face of population pressure whereby non-farm activities take precedence over farming as the basis of rural household livelihoods.…”
Section: Introductionmentioning
confidence: 99%